Na Putu ka Odrzivosti u Drzavama Bliskog Istoka: Spremnost za Energetsku Tranziciju - Minic, Aleksandra; Filipović, Sanja (The European Journal of Applied Economics, 2024)
Whilst stakeholders and policy makers in industry and academia increasingly use circular and sustainable, the terms are not clearly understood. Furthermore, the need for a switch from a current economic model (linear) to the circular one has been recognized globally by the major decision makers. The shift from one mechanism to another experiences challenges in grasping the Circular Economy (CE) and Sustainability (S) principles: defining them, understanding the similarities and differences, and successfully applying them using Triple Bottom Line (TBL) approach. Employing systematic literature review, the paper aims to clarify the ambiguities and add to clarity by exploring the concepts and the relationship of CE and S by applying TBL framework – social, environmental and economic variables. The gaps regarding relations to people and profit contribution are identified in the literature, and future research priorities and new framework recommended. Finally, the objective is to ascertain whether a strategic approach on sustainability and measures are in place in Gulf Cooperation Council (GCC), such as increased investment in renewable energy infrastructure that could positively affect energy transition readiness, evidenced by energy efficiency indicators (reduced carbon emissions). Hence, three GCC countries were selected, and their goals, and challenges explored, and further research recommended.